Creating language crimes : how law enforcement uses (and misuses) language - Shuy, Roger W. (Oxford University Press, 2005)
Roger Shuy illustrates how linguistic analysis of undercover tape recordings made by law enforcement can help defense attorneys, law enforcement officers, judges, and juries better understand the effects of conversational strategies used to give the appearance of criminal activity.